Implementation of Task-based Learning in Teaching English in Indonesia: Benefits and Problems - Sholeh, Muhammad Badrus (Universitas Negeri Semarang, 2020)
A variety of approaches exist in foreign language teaching and learning; Task-based Learning (TBL) is one of them. It is an innovative approach that is developed from the Communicative Approach. The concepts of TBL have proven successful in classrooms. In this study, the writer conducted a literature review of task-based learning in teaching English dealing with the benefits and problems in implementing this approach in Indonesia. This paper seeks to review Task-based Learning (TBL), covering the definition of ‘task’ and Task-based Learning (TBL), the characteristics and stages of TBL, the teacher and students’ roles in Task-based Learning, and also the advantages and disadvantages of Task-based Learning. It also addresses the application, the benefits and problems of Task-based Learning in the sense of Indonesian EFL context. This will help educators and language teachers in Indonesia to attach more importance to the contextual differences when applying Task-based Learning in Indonesia.